Neuropsychiatric disorders in chronic hepatitis C patients after receiving interferon or direct-acting antivirals: a nationwide cohort study - Fang, Yu; Chen, Chung-Yu; Yu, Hsien-Chung; Lin, Pei-Chin (Frontiers in Pharmacology, 2023)
Background: Data on the neuropsychological outcomes after receiving direct-acting antivirals (DAA) among chronic hepatitis C (CHC) patients was not well documented.Aim: To evaluate the difference in incidence of neuropsychological disorders (NPDs) after treatment completion between CHC patients receiving interferon (IFN) therapy and DAA therapy.Methods: A nationwide retrospective cohort study was performed using Taiwan National Health Insurance Research Database (NHIRD) between 2010 and 2018. CHC patients without preexisting mental disorders were included and divided into treatment (Tx)-naïve DAA group, retreatment (re-Tx) DAA group, and Tx-naïve IFN group based on their HCV therapy. Propensity score matching was used to balance baseline differences between groups. The primary outcome was the incidence of NPDs during 6 months after completion of therapy.Results: After one-to-one matching, there were 6461 pairs of patients selected from Tx-naïve DAA group and Tx-naïve IFN group, and 3792 pairs from re-Tx DAA group and Tx-naïve IFN group. A lower incidence of NPDs was observed in Tx-naïve DAA group when compared to Tx-naïve IFN group (HR=0.72, 95% CI= 0.55-0.94, P=0.017).The risk of NPDs did not differ between the re-Tx DAA group and the Tx-naïve IFN group (HR=0.74, 95% CI: 0.52-1.05, P=0.092).DAA therapy was associated with lower risk of NPDs when compared with IFN therapy among Tx-naïve CHC patients in a 6-month period after treatment completion, especially among the patients with younger age (not more than 65 years old), male gender, and cirrhosis.